2015
DOI: 10.1152/ajpheart.00726.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of AV coupling during human atrial fibrillation: role of atrial rate

Abstract: The causal relationship between atrial and ventricular activities during human atrial fibrillation (AF) is poorly understood. This study analyzed the effects of an increase in atrial rate on the link between atrial and ventricular activities during AF. Atrial and ventricular time series were determined in 14 patients during the spontaneous acceleration of the atrial rhythm at AF onset. The dynamic relationship between atrial and ventricular activities was quantified in terms of atrioventricular (AV) coupling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…First is a short time scale clustering of RR intervals, embedded in the overall map. These additional clusters correspond to alternation of RR intervals which has been noted before in some cases of AF [ 25 , 39 , 42 ], but remains to be mechanistically explained and clinically investigated further. One possible explanation is dual-pathway AV conduction [ 25 , 39 ]; another is a Wenckebach variant of conduction block in the AV node.…”
Section: Resultsmentioning
confidence: 55%
“…First is a short time scale clustering of RR intervals, embedded in the overall map. These additional clusters correspond to alternation of RR intervals which has been noted before in some cases of AF [ 25 , 39 , 42 ], but remains to be mechanistically explained and clinically investigated further. One possible explanation is dual-pathway AV conduction [ 25 , 39 ]; another is a Wenckebach variant of conduction block in the AV node.…”
Section: Resultsmentioning
confidence: 55%
“…The cardiovascular system model utilises patient-derived series to simulate AF. Incorporating dynamical models that simulate electrocardiogram signals or dual pathway atrioventricular nodal conduction [47][48][49][50] with the existing cardiovascular system model may allow to simulate the dependence of the cardiovascular response on the rate and regularity of ventricular activation in AF [51]. Elaborating the cardiovascular system model to simulate atrioventricular nodal dynamics and the evaluation of CF-LVAD support and validation of the results will be future work.…”
Section: Discussionmentioning
confidence: 99%
“…Electrograms with inadequate signal-to-noise ratio were excluded from subsequent analysis. Activation time series were automatically extracted from each bipolar electrogram as previously reported (Faes et al, 2002;Masè et al, 2015). Briefly, electrograms were pre-processed to remove ventricular interference, local atrial activation waves were identified by signal filtering and adaptive threshold crossing (Faes et al, 2002;Masè et al, 2015) and atrial activation times were estimated by measuring the barycenter of local activation waves (Faes et al, 2002).…”
Section: Proof-of-concept Application To Clinical Mapping Datamentioning
confidence: 99%
“…Indeed, although the use of an interpolation approach allows flexibility for pattern reconstruction, interpolation is more sensitive to activation time misdetections and noise effects, with respect to techniques based on model fitting (Bayly et al, 1998;Fitzgerald et al, 2003;Weber et al, 2010;Alcaine et al, 2014) or approaches that do not require activation time detection (Richter et al, 2011;Rodrigo et al, 2016;Alcaine et al, 2017;Luengo et al, 2019;Handa et al, 2020). In order to reduce inaccuracy in activation time estimations, activation waveforms from patient data were automatically identified by a well-established technique (Botteron and Smith, 1995;Faes et al, 2002), and activation times were set at the waveform barycenter (Faes et al, 2002;Masè et al, 2005Masè et al, , 2015. As suggested in several works (Holm et al, 1996;Faes et al, 2002;El Haddad et al, 2013;, the use of a morphology-based activation detection, such as the barycenter method, improves estimation accuracy in the presence of fragmented electrograms.…”
Section: Radial Basis Function-based Conduction Velocity Vector Approach For the Characterization Of Propagation Patternsmentioning
confidence: 99%